(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This research aims to analyze the impact of supply chain risk management on project performance in the construction sector in Saudi Arabia, by studying SABIC. The researcher used an analytical descriptive and questionnaire as a tool for collecting data from a sample of 30 respondents from SABIC staff and engineers. The questionnaire has been divided into three main axes: sources and types of supply chain risk, and the effect of supply chain risk management on project performance, practices, challenges and success factors for supply chain risk management. The data has been analyzed using descriptive, graded, broken and unit statistics. The study concluded that there was a positive and moral impact on the management of the chain of supply chain to perform the project in the construction and construction sector in Saudi Arabia. The study recommended that the concept and methodology for the risk management of supply chain at all stages of projects, and to benefit from technology and innovation in improving and developing the supply chain, communication and cooperation with all parties concerned with the supply chain, and commitment to standards Environmental, health and safety laws and safety related to the supply chain.